Antibiotic resistance patterns of coagulase-negative Staphylococcus (CoNS) isolates from a major teaching hospital in Kuala Lumpur, Malaysia - Asif Sukri,; Haifa Hanani Mohamad Zaki,; Noraziah Mohamad Zin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Coagulase-negative Staphylococcus (CoNS) species is a leading cause of nosocomial infection in patients with indwelling medical devices and immunocompromised patients. This study was conducted to determine the antibiotic resistance pattern of CoNS isolated from a major teaching hospital in Malaysia. A total of 43 CoNS isolates were collected from August to October 2018 at Hospital Canselor Tuanku Muhriz, Kuala Lumpur, Malaysia. Speciation of CoNS species was conducted by 16S rRNA sequencing. Antibiotic susceptibility test was performed using a standard procedure, and detection of staphylococcal cassette chromosome mec (SCCmec) elements and antibiotic resistance genes were conducted via multiplex polymerase chain reaction (PCR). Comparison of 16S rRNA sequences showed that 67.44% of the isolates were identified as S. epidermidis, followed by S. haemolyticus (11.63%), S. hominis (9.3%), S. capitis (4.65%), and other Staphylococcus sp. (6.98%). All the CoNS isolates were susceptible to linezolid and tedizolid, while most of them were resistant towards penicillin (86.05%), cefoxitin (69.77%), erythromycin (72.02%), and 88.37% of them were resistant to at least 3 antibiotics. The majority of CoNS harboured nontypeable SCCmec elements. AacA-D (95.5%) and ermC (78.6%) were the most commonly detected antibiotic resistance genes while no detection of tetK, tetM and ermA genes were observed. This study showed a high prevalence of multidrug-resistant CoNS in HCTM healthcare settings. Understanding CoNS resistance mechanism is warranted for intervention strategy.